HUBUNGAN PARITAS DAN ANEMIA DENGAN PERSALINAN PREMATUR - Riva'i, Syamsul Bahri; Ayuningtyas, Ratih; Shalsabillah, Thalia (Media Penelitian dan Pengembangan Kesehatan, 2024)
Premature birth is the main cause of high perinatal mortality rates. The lower the birth weight, the higher the incidence of morbidity and mortality. WHO says there are 15 million babies born prematurely every year throughout the world. Of the 15 million premature babies, 1.1 million babies were reported to have died due to various complications. Premature birth and complications in labor are always associated, such as asphyxia, infection and birth defects, which are the cause of most neonatal deaths. The aim of this study was to determine the relationship between parity and anemia with the incidence of preterm labor. This research is a quantitative observational analytical study with an individual matched case-control design, a retrospective approach using secondary data from mothers giving birth in the Obstetrics and Obstetrics Department of Arifin Achmad Hospital Riau for the period January 2016 – December 2018 which was carried out in May – June 2023. The sample size was 259 cases and 259 controls. From the parity chi-square test carried out, a p-value of 0.855 (≥ 0.05) was obtained, where it was concluded that there was no relationship between parity and the incidence of premature labor and from the chi-square test for anemia, a p-value of 0.00 was obtained ( <0.05) so it can be concluded that there is a relationship between anemia in pregnancy and OT at Arifin Achmad Hospital, Riau Province. It is recommended that pregnant women check their HB levels to avoid amenia which can cause premature labor and also to avoid other factors that cause premature labor.